Effects of Size of Zinc Borate on the Flame Retardant Properties of Intumescent Coatings - Ning Lu; Pengchao Zhang; Ya’nan Wu; Danqing Zhu; Zhu Pan (International Journal of Polymer Science)
This paper is aimed at assessing the fire retardancy and thermal stability of intumescent flame retardant (IFR) containing ammonium polyphosphate (APP), pentaerythritol (PER), and melamine (MEL). Zinc borate (ZB) was added at the loading of 2%, 4%, 6%, 8%, 10%, and 12% by weight of IFR. The sizes of investigated ZB fall in 3 ranges: 1-2 μm, 2-5 μm, and 5-10 μm. The performance of APP/PER/MEL was investigated by using thermogravimetry analysis (TGA), cone calorimeter test, Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy, and energy-dispersive spectrometry. The results obtained from the above experiments show that the incorporation of ZB can improve the fire protection performance. A 77% decrease in total smoke production and 84.6% decrease in total heat release were achieved for the addition of 2 wt% ZB (2-5 μm) in the IFR coating. TGA results indicate an increased amount of char residue. Compared to the control IFR coating, the char residue of IFR containing 2 wt% ZB (2-5 μm) has increased approximately 1.5-fold, 10-fold, and 25-fold, at 600°C, 700°C, and 800°C, respectively. The effective char formation results in excellent smoke suppression. Regarding smoke suppression performance, the order for smoke density is IFR/ZB (2-5 μm) < IFR/ZB (5-10 μm) < IFR/ZB (1-2 μm), regardless of investigated loading levels. The decline of smoke suppression performance for IFR/ZB (5-10 μm) and IFR/ZB (1-2 μm) is believed to be due to the poor char formation, as a result of a weak interaction of APP, PER, MEL, and ZB. This weak interaction is caused by the decrease in the specific surface area and agglomeration of ZB particles for IFR/ZB (5-10 μm) and IFR/ZB (1-2 μm), respectively.